2021
DOI: 10.3390/ijerph18041868
|View full text |Cite
|
Sign up to set email alerts
|

Innovating Occupational Safety Training: A Scoping Review on Digital Games and Possible Applications in Agriculture

Abstract: Digital games have been successfully applied in different working sectors as an occupational safety training method, but with a very limited application in agriculture. In agriculture and other productive sectors, unintentional injuries tend to occur with similar dynamics. A literature review was carried out to understand how occupational risks are addressed during game-based safety training in different productive sectors and how this can be transferred to agriculture. Literature about “serious game” and “gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 90 publications
(225 reference statements)
1
8
0
1
Order By: Relevance
“…However, concerns are growing about the viability of augmenting educational and training content with augmented reality-that is, whether translating the information to AR format is worthwhile [27]. Additionally, these findings support the earlier systematic review of 42 publications conducted by Vigoroso et al [6]. They demonstrated digital games could help operators improve their abilities and safety knowledge.…”
Section: Promising Trends For Pandemic-related Researchsupporting
confidence: 71%
See 1 more Smart Citation
“…However, concerns are growing about the viability of augmenting educational and training content with augmented reality-that is, whether translating the information to AR format is worthwhile [27]. Additionally, these findings support the earlier systematic review of 42 publications conducted by Vigoroso et al [6]. They demonstrated digital games could help operators improve their abilities and safety knowledge.…”
Section: Promising Trends For Pandemic-related Researchsupporting
confidence: 71%
“…Gamification is increasingly being utilized to educate participants in Occupational Safety and Health training on various aspects of workplace safety and risk. Prior research has established that gamification has been successfully used as an instruction delivery technique in the fields of safety, health and rehabilitation [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…We found that teachers assume that verbal learning is the easiest to achieve, followed by procedural and finally attitudinal learning . Therefore, we see teachers focus more on data and conceptual learning , as in most of the research on the educational use of VG ( Boyle et al., 2016 ; Clark et al., 2016 ; Vigoroso et al., 2021 ). This kind of learning represents a huge part of the content in the traditional curriculum, specifically the lower-level verbal learning ( data learning ) instead of more complex learning ( concept understanding ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely studied that VG improve verbal learnings in STEM areas (Science, Technology, Engineering, and Mathematics), especially factual knowledge over concept acquisition . This is also the case in second language learning or even in professional contexts ( Vigoroso et al., 2021 ). Some studies state that VG, and especially commercial off the shelf ones, have greater positive impacts when accompanied by scaffolding practices: instructional designs and interventions that mediate play ( Clark et al., 2016 ) and which provide added values for learning ( Barzilai and Blau, 2014 ; Mayer, 2019 ).…”
Section: Introductionmentioning
confidence: 89%
“…According to a review of the literature, gamification is increasingly being used to educate OSH training participants about different forms of workplace safety and risk. For example, research by Vigoroso et al [34] demonstrated that gamification, as a method of delivering training, has been successfully implemented in safety, health, and rehabilitation. Shirokov [35] argued that a high volume of occupational safety and health training material can increase the cognitive load on training participants.…”
Section: Osh Training With Technologymentioning
confidence: 99%